2014
DOI: 10.5194/isprsarchives-xl-3-305-2014
|View full text |Cite
|
Sign up to set email alerts
|

Structure-from-motion for MAV image sequence analysis with photogrammetric applications

Abstract: MAV systems have found increased attention in the photogrammetric community as an (autonomous) image acquisition platform for accurate 3D reconstruction. For an accurate reconstruction in feasible time, the acquired imagery requires specialized SfM software. Current systems typically use high-resolution sensors in pre-planned flight missions from far distance. We describe and evaluate a new SfM pipeline specifically designed for sequential, close-distance, and low-resolution imagery from mobile cameras with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 35 publications
(38 reference statements)
1
13
0
Order By: Relevance
“…But is computationally expensive requiring O((N c + N 3D ) 3 ) operations for N c cameras or views and N 3D structure, 3D scene feature or tie points (cubic in time and quadratic in memory). Conventional BA shows satisfactory convergence if sufficiently accurate initial estimates are provided either from image feature matching-based essential matrix estimation [23,1] or combined with on-board sensor measurements [29,15,45].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…But is computationally expensive requiring O((N c + N 3D ) 3 ) operations for N c cameras or views and N 3D structure, 3D scene feature or tie points (cubic in time and quadratic in memory). Conventional BA shows satisfactory convergence if sufficiently accurate initial estimates are provided either from image feature matching-based essential matrix estimation [23,1] or combined with on-board sensor measurements [29,15,45].…”
Section: Introductionmentioning
confidence: 94%
“…We show that weak camera parameters provided by inaccurate sensors on airborne platforms can be directly used for BA as initial values (and not as extra constraints [29,15,45]), provided that a proper robust function is used. It will be shown that there is no need to apply a camera estimation method (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the UAV pre-processing procedures, i.e. image stitching (Li, Hui et al 2015;Xu et al 2016; and 3D reconstruction (Turner, Lucieer, and Christopher 2012;Schönberger, Fraundorfer, and Frahm 2014), output extremely large-scale Digital Orthophoto Map (panorama or DOM) with VHR. The panorama or DOM can provide a global and detailed inspection of the investigative area.…”
Section: Motivation and Objectivementioning
confidence: 99%
“…However, Sun et al (2016) parameterize oblique camera poses with nadir camera poses as well as constant relative poses between oblique and nadir cameras, so that the number of unknown parameters and the dimension of the normal equations decrease, which dramatically reduces the computational complexity and memory cost. Relative observations that relate the position and attitude parameters of two consecutive epochs are exploited by Rehak (2017) as well as by Schönberger et al (2014) in the UAV case. Klingner et al (2013) optimize trajectories from Google Street View cars by leveraging precise relative poses from IMU.…”
Section: Introductionmentioning
confidence: 99%